A low cost pc-based voltammetric analyzer for determination of cadmium, copper, lead, nickel, zinc and other trace elements in water - Montoya, Eduardo (2002)
Anodic-stripping voltammetry, like as other electro-analytical techniques of chemical analysis can be very valuable as complements for neutron activation analysis (NAA), for rapid, accurate and simultaneous determination of some trace elements in water and in digested biological samples at the ppb(g/L) range. Commercial voltammetric analyzers may have a cost in the range of US$ 20,000.00 and the limited budget of our NAA laboratory not allow us to buy this kind of complementary instrumentation. In this paper we describe a PC- based voltammetric analyzer, designed and built in our laboratories at a relatively low cost.